Lymfedémy po operacích karcinomu vulvy. Prospektivní studie - Nováčková, M; Halaška, M J; Malá, I; Robová, H; Pluta, M; Chmel, R; Rob, L (Ceska gynekologie, 2013)
INTRODUCTION: Prospective detection of postoperative lymphedema of the lower limbs (LLL) in patients after surgery for vulvar cancer using different examination methods and their comparison. DESIGN: Prospective clinical study. SETTING: Department of Obstetrics and Gynecology, 2nd Medical Faculty of the Charles University and University Hospital Motol, Prague. METHODS: Totally 36 women were followed after surgery for vulvar cancer. Due to the radicality of surgery the patients were divided into conservative (sentinel lymph node biopsy) and radical (inguinofemoral lymphadenectomy) group. Lower limbs were preoperatively and 3, 6 and 12 months after surgery assessed for the presence of lymphedema by measuring of circumferences, multifrequency bioelectrical impedance analysis (MFBIA) and subjective evaluation of patients. RESULTS: The prevalence of lower limb lymphedema 12 months after surgery diagnosed by subjective evaluation reached 19,44%, by circumference measurement 38,89% and with MFBIA 66,67%. The prevalence of lymphedema after inguinofemoral lymphadenectomy diagnosed by circumference measurement was in 12 months after surgery higher (45.83%) than after the conservative surgery (25%). Risk factors were evaluated 12 months after surgery (age, BMI, adjuvant radiotherapy, type of surgery) and none of them were found to be statistically significant for the development of the lower limbs lymphedema. CONCLUSION: The prevalence of lymphedema significantly depends on the diagnostic method, because they capture lymphedema in its various stages. Due to the high sensitivity MFBIA can be used for the detection of early stages of lymphedema. Preoperative measurement of the lower limbs is important for early detection of postoperative lymphedema.
Keywords: dolní končetina; nádory vulvy; Czech Republic; senioři; lymfedém; Vulvar Neoplasms; Humans; Female; lidé; Prospective Studies; Middle Aged; ženské pohlaví; lidé středního věku; Gynecologic Surgical Procedures; Česká republika; Prevalence; rizikové faktory; prospektivní studie; gynekologické chirurgické výkony; Lower Extremity; Risk Factors; dospělí; Adult; Lymphedema; prevalence; Aged